2014
DOI: 10.1055/s-0033-1338635
|View full text |Cite
|
Sign up to set email alerts
|

Design and Development of Ligands for Palladium-Catalyzed Carbonylation Reactions

Abstract: The palladium-catalyzed carbonylation reaction remains a challenging and significant research field in organic chemistry, and has emerged as a powerful and straightforward protocol for the preparation of various bioactive carbonyl compounds under quite mild reaction conditions. The achievements in this area are correlated to the design and development of versatile ligands that not only facilitate the catalytic transformation, but also provide additional control over the selectivity of the reactions. In this co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(7 citation statements)
references
References 80 publications
0
7
0
Order By: Relevance
“…According to previously described [49,51,[61][62][63][64], a simplified mechanism for the formation of 4-amide substituted phthalonitrile is proposed in Figure 1 All carboxamide substituted phthalonitriles were characterized by 1 H, 13 C-NMR and mass spectrometry and their structures confirmed. It is worth mentioning that, under the reaction conditions employed (100 • C and 5 bar), 100% chemoselectivity toward the mono-carboxamide products was obtained, since no double carbon monoxide insertion product was observed, using these amines as nucleophiles [55,65].…”
Section: Resultsmentioning
confidence: 79%
“…According to previously described [49,51,[61][62][63][64], a simplified mechanism for the formation of 4-amide substituted phthalonitrile is proposed in Figure 1 All carboxamide substituted phthalonitriles were characterized by 1 H, 13 C-NMR and mass spectrometry and their structures confirmed. It is worth mentioning that, under the reaction conditions employed (100 • C and 5 bar), 100% chemoselectivity toward the mono-carboxamide products was obtained, since no double carbon monoxide insertion product was observed, using these amines as nucleophiles [55,65].…”
Section: Resultsmentioning
confidence: 79%
“…One major reason for the requirement of high palladium catalyst loadings is the fast formation of palladium black (catalyst bleach) under carbon monoxide. Thus, the development of new ligands and more stable catalyst systems are important to solve the high catalyst loading issue . Also, finding more benign oxidant systems is highly sought after for oxidative carbonylations.…”
Section: Palladium-catalyzed Carbonylations In Streamlining Complex N...mentioning
confidence: 99%
“…In 1974, Heck and co-workers reported that activated halides can react with carbon monoxide and alcohols (or amines) to form esters (or amides) in the presence of a palladium catalyst . Since this seminal discovery, palladium-catalyzed carbonylation reactions have become a popular topic among the synthetic community with new and enabling methods constantly being developed . While other transition metals can also participate in carbonylation chemistry, palladium-based carbonylation methods have been the most diverse, extensively developed, and utilized in organic synthesis.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[25][26][27][28][29][30][31][32] In 2018, we reported a novel and efficient synthesis and resolution of structurally interesting oxa-spirocyclic diphenols (O-SPINOL, >100 g scale), and the related ligand O-SpiroPAP showed excellent efficacy in the dynamic kinetic resolution of Bringmann's lactone. 33 The crystal structure of O-SPINOL shows that the introduction of oxygen atoms to the spirocyclic moiety makes a great difference, and the distance between the two phenolic oxygens in O-SPINOL becomes longer compared to that same distance in SPINOL and other related spiro diphenols (Figure 1), 13,14,31,32 which is expected to result in a larger bite angle [34][35][36][37][38][39][40] and higher electron density at the P atoms of the corresponding diphosphine. Herein, we report the design and synthesis of O-SDP as rigid diphosphine with a wider bite angle compared with SDP and its synthetic applications.…”
Section: Introductionmentioning
confidence: 99%